2017
DOI: 10.1037/pla0000050
|View full text |Cite
|
Sign up to set email alerts
|

Four approaches to using sandtray in play therapy supervision.

Abstract: Sandtray is an expressive intervention used in play therapy that may also be used to enhance play therapy supervision. This article presents four approaches to using sandtray in play therapy supervision. These approaches include teaching sandtray as an intervention, promoting supervisee self-awareness, case consultation, and group supervision. The authors highlight the purpose of play therapy supervision and present the Integrated Development Model (Stoltenberg & McNeill, 2010) as a way of conceptualizing supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One qualitative research article examined supervisors’ perceptions of play therapy supervision (Glazer & Stein, 2015). Supervision topics in nonresearch articles included therapeutic factors ( n = 2), such as empathy (Stulmaker, Lertora, & Garza, 2015) and genuineness (Blanco, Muro, & Stickley, 2014) in supervision; explanations of supervision modalities ( n = 4), such as sand tray (Hartwig & Bennett, 2017; Perryman, Moss, & Anderson, 2016) and expressive arts (Purswell & Stulmaker, 2015); and operationalization of play therapy supervision ( n = 2).…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative research article examined supervisors’ perceptions of play therapy supervision (Glazer & Stein, 2015). Supervision topics in nonresearch articles included therapeutic factors ( n = 2), such as empathy (Stulmaker, Lertora, & Garza, 2015) and genuineness (Blanco, Muro, & Stickley, 2014) in supervision; explanations of supervision modalities ( n = 4), such as sand tray (Hartwig & Bennett, 2017; Perryman, Moss, & Anderson, 2016) and expressive arts (Purswell & Stulmaker, 2015); and operationalization of play therapy supervision ( n = 2).…”
Section: Discussionmentioning
confidence: 99%
“…Other mental health associations and practitioners have addressed the importance of standards, including competencies, specific to their unique modalities. Hartwig and Bennett (2017), among other authors, have also indicated the need for addressing these critical components. Research-based competencies are identified by the Association for Play Therapy as part of its credentialing process (APT, 2022;Turner et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 98%
“…After participating in three sandtray experiences during their supervised clinical work, participants reported themes of group cohesiveness and emotionality, where the participants processed their emotions regarding stressful events. Additionally, sandtray therapy has been utilized to facilitate students' multicultural development (Paone et al, 2015) through online supervision to foster connection and enhance therapist competence (Villarreal-Davis et al, 2021) and is suggested as an effective way to facilitate therapist self-awareness within play therapy supervision (Bratton et al, 2008;Hartwig & Bennett, 2017). Anekstein et al (2014) outlined a seven-step implementation of sandtray supervision within Bernard's (1979) DM for counselors-in-training.…”
Section: Sandtray Within Supervisionmentioning
confidence: 99%